The Influence of The Hangman Game on The Students’ Vocabulary Mastery For 10th Grade of SMAN 8 Jambi - Bryan, Christoper; Suyadi, Suyadi; Munawwaroh, Khidayatul (Universitas Batanghari Jambi, 2025)
This research aims to investigate the influence of the Hangman game on the vocabulary mastery of 10th-grade students at SMAN 8 Jambi City. The study was conducted using a pre-experimental method with two groups of classes: an experimental class taught using the Hangman game and a control class taught using the conventional methods. Data were collected through a test administered before and after the treatment. The results revealed that the students in the experimental class showed an improvement in their vocabulary mastery. These findings suggest that incorporating the Hangman game as a supplementary teaching strategy not only improves learning outcomes but also motivates students through active participation and enjoyable practice. Therefore, it is suggested that English teachers should consider implementing the Hangman game or a similar interactive game to create a more engaging learning environment.